“IGT-like” status in normoglucose tolerant obese children and adolescents: the additive role of glucose profile morphology and 2-hours glucose concentration during the oral glucose tolerance test - Olivieri, Francesca; Zusi, Chiara; Morandi, Anita; Corradi, Massimiliano; Boselli, Maria L.; Fornari, Elena; Bonadonna, Riccardo C.; Maffeis, Claudio (International Journal of Obesity, 2019)
Objective To assess whether combining glucose shape and 2-h glucose concentration during an oral glucose tolerance test (OGTT) may help identifying normal glucose tolerant obese children/adolescents with an impaired glucose tolerant (IGT)-like metabolic profile in term of insulin sensitivity (Matsuda index) and β-cell function (disposition index: DI). Subjects, methods, and main outcome measure In total, 654 non-diabetic obese children/adolescents underwent a 2 h OGTT. The whole population was classified according to 2-hour plasma glucose ( < 100, 100–119, 120–139, 140–200 mg/dL) and glucose shape (monophasic or biphasic). Monophasic morphology was characterized by an increase in OGTT glucose concentration followed by a decline of at least 4.5 mg/dL, a biphasic response was defined as a decrease in glucose after an initial increase, followed by a second increase of ≥ 4.5 mg/dL. A subset of 69 participants had also a prolonged OGTT to estimate β-cell function in “biphasic” versus “monophasic” patients. Results Matsuda index and DI decreased across 2-h glucose categories (both p < 0.001) and were lower in monophasic compared with biphasic children, independently of 2-h glucose category (both p < 0.001, both p for glucose category×shape interaction > 0.05). Normal glucose tolerant children with 2-h glucose of 120–139 mg/dl and monophasic glucose shape did not differ from IGT children, as regards Matsuda index and DI (both p > 0.05). Among children undergoing a prolonged OGTT, those with a monophasic glucose shape had worse β-cell function, modeled as proportional control, than those with a biphasic shape ( p = 0.031). Conclusions A monophasic OGTT glucose shape is associated with unfavorable glucose metabolism independently of 2-h glucose concentration. Children combining monophasic shape and normal-high 2-h glucose have an IGT-like glucose metabolism.